ACCESS TO IMPROVED SANITATION: IMPLICATION FOR SUSTAINABLE IMPLEMENTATION OF HYGIENE PRACTICES SECONDARY SCHOOLS IN MACHAKOS COUNTY, KENYA - Snow Eliud Mbula; Angeline Sabina Mulwa; Dorothy Ndunge Kyalo (European Scientific Journal, ESJ, 2014)
The purpose of the study was to investigate the extent to which access to improved sanitation influences the implementation of hygiene practices in public secondary schools in Machakos County with a view to come up with practical and affordable strategies for achievement of Millennium Development Goals(MDGs) on sanitation. The study was guided by the following research questions: To what extent does the (i) type,(ii) maintenance and(iii) adequacy of sanitation facilities influence sustainable implementation of hygiene practices in public secondary schools in Machakos County. Descriptive survey research design was adopted. A sample size of 28 schools, 354 students and 28 principals was selected by use of simple random sampling from a target population of 30 schools, 4481 students and 30 principals from Central Division. A questionnaire and an interview schedule were used to collect data. Data was analyzed by using descriptive statistics for quantitative data, by use of frequency tables, percentages and measures of central tendency. Hypotheses was tested using one way analysis of variance (ANOVA) since hygiene practice as the dependent variable was measured at interval scale while the independent variables were measured at the nominal scale. Regression prediction models were developed for estimating implementation of hygiene practices. The study established that availability of sanitation facilities in public secondary schools was a significant factor in determining the extent of implementation of hygiene practices in such schools and indeed any other learning institution. Availability of sanitation facilities accounted for 60.1 percent of the change in the level of implementation of hygiene factors in secondary schools. The study recommends that the Ministry of Education and the school management should ensure adequate number of sanitation facilities in every school. The sanitation facility should be appropriate for both normal students and students with special needs, and be located at site where privacy of the users is ensured. This will ensure effective implementation of hygiene practices by both students and other members in the school community.